Microangiopathic haemolytic anaemia associated with malignant haemangio-endothelioma. Issue 5 (July 1971) - Donald, D.; Dawson, Audrey A.
Abstract : A case of microangiopathic haemolytic anaemia associated with malignant haemangio-endothelioma is described. It is suggested that haemolysis may have been due to mechanical trauma sustained by the red blood cells on passage through the tumour's abnormal vasculature.